2009
DOI: 10.1002/clc.20307
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Dual Antiplatelet Therapy Improves Clinical Outcomes in High‐risk Patients Implanted with Sirolimus‐eluting Stents

Abstract: BackgroundAlthough a science advisory recommending 12 months of dual antiplatelet therapy after drug‐eluting stents implantation was published recently, the optimal duration of dual antiplatelet therapy has not yet been precisely determined.HypothesisProlonged dual antiplatelet therapy can improve clinical outcomes in high‐risk patients implanted with sirolimus‐eluting stents.MethodsThe patients implanted with sirolimus‐eluting stents were assigned into standard clopidogrel therapy group (clopidogrel 75 mg/d f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…7 Although the advised duration of dual antiplatelet regimens is 12 months, the optimum duration is controversial. 8,9 For example, long-term (> 4 weeks) dual antiplatelet therapy with clopidogrel and aspirin after percutaneous coronary intervention (PCI) was found to be associated with an increased incidence of gastrointestinal complications and, although not associated with a significant increase in the overall incidence of bleeding events, there was an increase in major gastrointestinal bleeding in the year after a PCI. 10 A higher dose of clopidogrel for a period of 12 months after implantation of a drug-eluting stent was found to be associated with a greater risk of subsequent bleeding events.…”
Section: Discussionmentioning
confidence: 97%
“…7 Although the advised duration of dual antiplatelet regimens is 12 months, the optimum duration is controversial. 8,9 For example, long-term (> 4 weeks) dual antiplatelet therapy with clopidogrel and aspirin after percutaneous coronary intervention (PCI) was found to be associated with an increased incidence of gastrointestinal complications and, although not associated with a significant increase in the overall incidence of bleeding events, there was an increase in major gastrointestinal bleeding in the year after a PCI. 10 A higher dose of clopidogrel for a period of 12 months after implantation of a drug-eluting stent was found to be associated with a greater risk of subsequent bleeding events.…”
Section: Discussionmentioning
confidence: 97%
“…There are 2 possible explanations for the increased incidence of bleeding events observed in the present study. First, as mentioned above, older age is a significant predictor of bleeding . The current study included only patients aged ≥80 years, which could have contributed to the higher incidence of bleeding events relative to those reported by previous investigators.…”
Section: Discussionmentioning
confidence: 93%
“…Long‐term DAT is required to prevent stent thrombosis following DES implantation . However, DAT is associated with the potential risk of bleeding events, particularly in octogenarians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 34 studies were identified, including 7 randomized trials (with 2 ongoing) and 1 meta‐analysis, thus leaving 26 nonrandomized controlled studies (Table 5). 16,19–20,23–50 A total of 208,670 patients were included, and 28,345 will be enrolled in currently ongoing studies. Clinical trials were not unanimously in favor or against DAT beyond 6–12 months.…”
Section: Discussionmentioning
confidence: 99%